Applicability of Brazilian reference equations for the 6-minute walk test in patients with lung cancer (Fisioterapia e Pesquisa, 2020)
The aim of this study was to verify the impact of using different Brazilian reference equations for the distance covered in the 6-minute walk test (6MWT) in the evaluation of functional exercise capacity in patients with lung cancer (LC). This cross-sectional study included 48 patients with LC (average age of 60±12 years-old). The participants underwent an assessment of sociodemographic and clinical characteristics and their functional exercise capacity with the 6MWT, following international recommendations. Five equations were analyzed. The distance covered by the patients (503±102 meters) was relatively close to the distances predicted by the reference equations (82-94% of the predicted), although statistically lower (p<0.05 for all).